2018
DOI: 10.1007/s11695-018-3473-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy for Obesity in Polycystic Ovarian Syndrome: a Pilot Study Evaluating Weight Loss and Fertility Outcomes

Abstract: Compared to non-PCOS patients, PCOS patients had greater postoperative ΔBMI and %EWL at 1 year. The majority of patients becoming pregnant after VSG were previously nulliparous. This study shows that VSG is effective for weight loss in PCOS patients with obesity and may positively augment effect fertility rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Dilday et al investigated the outcomes of sleeve gastrectomy in patients with PCOS related to weight loss and fertility. Through 119 PCOS patients, they demonstrated that most of the PCOS patients became pregnant after the operation, with an effective weight loss and weight control [16].…”
Section: Discussionmentioning
confidence: 99%
“…Dilday et al investigated the outcomes of sleeve gastrectomy in patients with PCOS related to weight loss and fertility. Through 119 PCOS patients, they demonstrated that most of the PCOS patients became pregnant after the operation, with an effective weight loss and weight control [16].…”
Section: Discussionmentioning
confidence: 99%
“…These hormonal changes were also associated with the regulation of the menstrual cycle and resolution of dysmenorrhea [45]. Moreover, 22% percent of PCOS patients became pregnant within 12 months, 69% of which were previously nulliparous [43].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 94%
“…Polycystic ovarian syndrome (PCOS) is a common endocrine disorder associated with obesity. Women with PCOS have hyperandrogenism and hyperinsulinemia with subsequent insulin resistance and infertility [43]. LSG is effective in treating PCOS, resulting not only in WL, but also significant improvement in the hormonal profile [43,44].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
See 2 more Smart Citations